Against the Big Society: A Durkheimian socialist critique. (February 2013) - Dawson, Matt
This paper is an attempt to take a critical sociological look at the UK government's flagship 'Big Society' policy. To do this I utilize the political sociology of Émile Durkheim, specifically what I call his 'socialist theory'. This overlooked aspect of Durkheim's sociology contains a strong normative critique and alternative project concerning the role of the State, private property, economic regulation and inequality. By applying this to the Big Society it is argued that the latter will result in: increased moral fragmentation, the furthering of economic inequality and the development of a 'postcode lottery'. Instead, Durkheim's advocacy of functional representation in the form of the 'corporations' seems to hold some contemporary relevance.